Rosettes in T-cell pseudolymphoma: a new dermoscopic finding, - Rodrigo Gomes Alves; Patricia Mayumi Ogawa; Mílvia Maria Simões e Silva Enokihara; Sergio Henrique Hirata (Sociedade Brasileira de Dermatologia, 2021)
Abstract Rosettes are small white structures visible with polarized light dermoscopy, whose exact morphological correlation is not yet defined. These small shiny structures are found in several conditions such as scarring, dermatofibroma, molluscum contagiosum, squamous cell carcinoma, basal cell carcinoma, melanoma, melanocytic nevus, discoid lupus erythematosus, and papulopustular rosacea. In this novel report, the authors describe the presence of rosettes in a T-cell pseudolymphoma lesion.